Come find me - Miranda, Megan (New York : Crown, 2019)
Told in two voices, sixteen-year-old Kennedy Jones and seventeen-year-old Nolan Chandler are drawn together by strange signals related to family tragedies, and find they are more connected than they could have imagined.
Keywords: Supernatural -- Fiction; Brothers and sisters -- Fiction; Missing children -- Fiction; Death -- Fiction; Family problems -- Fiction